Factors Related to Adherence to Taking Anti-Tuberculosis (OAT) Drugs in Pulmonary Tuberculosis Patients at Cut Meutia General Hospital, North Aceh Regency - Sahputri, Juwita; Cut Khairunnisa (Open Access Indonesian Journal of Medical Reviews, 2022)
Tuberculosis (TB) is a disease with a high risk of transmission and is one of the diseases whose cases continue to increase and cause death worldwide. Until now, pulmonary tuberculosis has been difficult to treat because of the patient's non-compliance with taking anti-tuberculosis drugs (OAT). This study aims to investigate the factors associated with adherence to taking OAT drugs in tuberculosis patients at Cut Meutia General Hospital. This research is an observational study with a cross-sectional design. The study was conducted at the pulmonary disease polyclinic of Cut Meutia General Hospital, North Aceh Regency. The study was conducted on 100 patients, with the sampling technique being total sampling. The sample inclusion criteria in this study were patients who had been diagnosed with pulmonary tuberculosis, were willing to participate in the study, and had signed an agreement to participate in the study. A total of 100 patients participated in this study. Most of the patients were male (64%), aged over 46 years (52%), had low education (75%), had difficult hospital access (70%), and had poor knowledge regarding TB treatment (60%). In conclusion, the factors of age, gender, and distance of residence are related to adherence to taking OAT. Meanwhile, education and knowledge are not related to adherence to taking OAT in pulmonary TB patients at Cut Meutia General Hospital, North Aceh Regency.